Case management: Continuous Midwifery Care for Mrs. S. At Independent Midwife Practice Place/ TPMB (Tempat Praktek Mandiri Bidan) Ida Nopiah Salipah, S.Keb., Bdn Padurenan Mustika Jaya Bekasi - Sugiyono, Iis; Lisa Trina Arlym; Ida Nopiah Salipah; Rukmaini (International Journal of Midwifery and Health Sciences, 2025)
This care uses Continuity Of Care (COC) for Mrs. S since the third trimester of pregnancy, postpartum, and the neonate with the implementation of complementary care. The results obtained by Mrs. S during pregnancy went well, but at the beginning of the visit she experienced discomfort in the form of frequent urination and vaginal discharge so she was given Kegel exercise care and cleaning with boiled betel leaf water. The third visit, Mrs. S experienced Braxton Hix contractions, so she was given relaxation techniques care. The delivery took place spontaneously vaginally on April 17, 2025. In the active phase I Mrs. S was restless because she felt pain, so she was given education on relaxation techniques, rebozo shake apple the tree, and massage. The duration of labor was 4 hours and 48 minutes. Postpartum monitoring was carried out until the 42nd day, and the involution process went well. The first day of breastfeeding was not smooth, so oxytocin massage was carried out and taught. During the neonatal period, the baby's condition was crying loudly, active muscle tone, reddish skin color, male gender, BB: 2990 grams, PB: 48 cm with Apgar Score 8/9, IMD had been carried out for 1 hour, given vitamin K prophylaxis, eye ointment, HB0 immunization, and in KN1–KN 4, Mrs. S's baby did not experience any complaints. It can be concluded that Mrs. S's pregnancy, labor, postpartum, and neonatal period were normal, no complications were found, and complementary care had been given according to the mother's needs.